An analysis of business intelligence for improved public service delivery - Hartley, Mogamat Kaashief (Department of Information Systems, 2015)
The public sector can be described with different types of public policies and by the services the organisations deliver to citizens. Public sector organisations are implementing e-government projects as mechanisms to enhance public service delivery. However, public sector e-government projects in developing countries are highlighted as challenging. Awards of achievement for implementing e-government projects have been noted in the South African public sector. Business Intelligence (BI) for improved public service delivery has been identified as a key tool to improve decision-making processes. Implementing BI in organisations has been revealed as complex. The study of organisational factors that influence the initiative for successful BI implementation is suggested. For this reason, the research sets out to explore the implementation of BI in the public sector in South Africa. The research was conducted through two case studies. Data was collected by conducting semi-structured interviews and document collection with organisations that are implementing BI. A qualitative thematic analysis method was used to construct the major themes that emerged from the data. The research objectives were addressed by constructing three frameworks; to describe what organisational factors influence the BI initiative, the factors that influence the use of BI, and a framework describing the process of implementing BI in the public sector. The Design-Reality gap model was applied to identify risk in the BI projects. The study revealed that BI can be used as an enabler of change and improvement in public sector activities. Consolidating structures, systems and processes was identified as a precursor to implementing BI. However, the level of skills to use BI tools was highlighted as key factor in hindering BI use.